OPTIMALISASI PENGELOLAAN KEUANGAN MELALUI PENERAPAN AKUNTANSI STRATEGIS PADA HOTEL BERBINTANG DI YOGYAKARTA - Yohanes Martono Widagdo; Agung Wibiyanto; Raditya Faiza Ramadhan; Anggun Jayanti (FIP UNIRA MALANG, 2026)
Effective financial management is the cornerstone of the hospitality industry’s sustainability and competitiveness. However, financial management at some hotels still focuses primarily on transaction recording and financial reporting, meaning that the use of financial information as a tool for strategic decision-making has not yet been optimized. This community service initiative aims to enhance hotel financial managers' understanding of the application of strategic accounting. The initiative was carried out in collaboration with the Association of Hotel Finance and Accounting Managers (AMKAH) in Yogyakarta through the following stages: needs assessment, training, workshops, implementation support, and monitoring and evaluation. The material covered included the use of financial statements as a managerial tool, operational cost control, and the optimization of cash flow management., The activity successfully improved participants' understanding of the application of strategic accounting, improved ability to achieve operational cost efficiency, and strengthened cash flow management as the foundation for developing hotel business strategies. Additionally, the implementation of strategic accounting contributes to improved financial management effectiveness and growth in hotel profitability. Thus, the implementation of this program supports the creation of more efficient, measurable, and sustainable hotel financial management. Keywords: strategic accounting; financial management; star-rated hotels; cost efficiency; cash flow.